The impact of allergies and smoking status on nasal mucosa of hypertrophied turbinates – an immunohistologic analysis. (11th May 2020) - Warman, Meir; Tiomkin, Evelyn; Huszar, Monica; Halperin, Doron; Asher, Ilan; Cohen, Oded
Abstract: Background: Allergies and smoking are common reasons for nasal mucosa inflammations, which in turn, cause nasal obstructions. Nevertheless, the impact of coexisting allergies and smoking on nasal mucosa inflammation has not been studied. Objectives: To study the impact of smoking with relation to allergies on nasal mucosa histology and to characterize an immunologic profile using immunohistochemical (IHC) staining. Methods: A cross-sectional study. Nasal biopsies of inferior turbinates from smokers with different allergic statuses were compared. Demographics, comorbidities, histologic, and immunohistochemical (IHC) staining of CD3, CD68, CD 20, and CD138 receptors were compared and analyzed. Results: A total of 53 patients were included, of which 20 (37.7%) were smokers, and 20 (37.7%) had allergic backgrounds. Smokers, both allergic and non-allergic, demonstrated reduced edema compared to the control group ( p Value = 0.034) and significantly lower eosinophil density in the stroma compared to the allergic nonsmokers' group ( p Value = 0.04). Smokers had a significant negative correlation between the number of cigarettes per day and the expression of CD20 in the stroma (−0.452, p Value = 0.045) and the epithelium (−0.432, p Value = 0.057) in IHC staining. Allergic smokers had a negative correlation (−0.705, p Value = 0.023) between the number of cigarettes per day and the CD68 marked cell expression in the epithelium. Conclusion: The coexistence of an allergic background and smoking alters known immunologic responses within the nasal mucosa. Smoking may have an immunosuppressive role in the nasal mucosa in both innate and humoral immune systems.